Planning of Indoor Femtocell Network for LTE 2300 MHz on Railways Carriages Using Radiowave Propagation Simulator 5.4 - Adisti Nabilah Naufallia; Anggun Fitrian Isnawati; Khoirun Ni’amah (JURNAL INFOTEL, 2021)
The indoor communication system is a system to solve the problem of weak signals received by placing a Femtocell Access Point (FAP) indoor area. The design of an indoor cellular communication network system is carried out using the Radiowave Propagation Simulator 5.4. The parameters observed were Received Signal Level (RSL) and Signal to Interface Ratio (SIR). The case study is the passenger carriage of the executive, business and economy passenger class. The research includes link budget calculations based on coverage and capacity by considering the type of train carriage material and train passenger capacity. The calculation results based on capacity obtained 1 FAP for executive and business class train passenger cars, while economy class train passenger cars obtained 2 FAP. The best scenario for executive class namely scenario 1A, the receiver gets average RSL of approximately -32.26 dBm and SIR of 0 dB. The best scenario for business class namely scenario 2A, the receiver gets average RSL of approximately -32.57 dBm and SIR of 0 dB. The best scenario for economy class namely scenario 3A, the receiver gets average RSL of approximately -29.80 dBm and the receiver gets average SIR of approximately 6.97 dB